Diagnosis Of Learning Difficulties From The Perspective Of The Quran - Tanuri; Khotimah, Husnul; Mujiono; Sharehan Alkhattab (Al-Mubin, 2024)
This research aims to determine the learning difficulties experienced by a student from the perspective of the Koran. Learning difficulties can be influenced by various factors, ranging from learning styles, learning concentration problems, having unique learning preferences, different learning methods, health problems, lack of student motivation to learn, environmental problems, and emotional problems and interest in learning. As a basis for the analysis, verses originate from the Koran. If the learning methods do not suit a person's learning style, they may need help understanding and retaining information. Therefore, individuals need to know their learning styles to adopt appropriate learning strategies for the analysis of verses originating from the Koran. This research is library-based, using qualitative methods and data sources from journal articles, books, or observations of phenomena occurring in the world of education today